Synthesis and Pharmacological Studies of Mixed Ligand Complexes of Lanthanide(III) Ions with Schiff Base and Diphenyl Sulphoxide - RAJENDRAN, G.; USHADEVI, K.G. (Asian Journal of Chemistry, 2010)
The present research paper is concerned with the synthesis and antimicrobial studies of some mixed ligand complexes of certain lanthanide(III) ions with a Schiff base and diphenyl sulphoxide. They are characterized on the basis of elemental analysis, molar conductances, molecular mass, and metal percentage, magnetic moments and spectral investigations (electronic and infrared spectra). Antimicrobial activity of the complexes was studied. The complexes conform to the composition [Ln(MDDA)3- (DPSO)X3] where X = NO3- or NCS- [Ln(MDDA)4(DPSO)X2]X where X = CIO4-. The Schiff base 4-methoxy-4'(N,N-dimethylamino) diphenyl azomethine (MDDA) is derived by the condensation of p-anisidine and p-dimethyl amino benzaldehyde. Both the Schiff base and DPSO act as neutral monodentate ligands and the complexes appear to be seven-coordinated. The infrared data suggest coordination of the ligand to the metal ions in a unidentate fashion through the nitrogen atom of the azomethine group and oxygen atom of the diphenyl sulphoxide molecule. The antimicrobial screening of the ligands and their complexes has been carried out Thermal decompositions were studied by TG and DTG techniques.